A Content Analysis of Research Articles in The Journal for Specialists in Group Work: 1998–2015. Issue 2 (3rd April 2017) - Stroud, Daniel; Pennington, Pete; Cleaver, Christopher; Collins, Janey-Rae; Terry, Nicholas
Abstract : We assessed research articles ( N  = 118) published in The Journal for Specialists in Group Work (JSGW) . Quantitative, qualitative, and mixed-methods studies were coded based on author, research topic, sample, and method characteristics. Over time the proportion of research articles have doubled, while practitioner authorship contributions have decreased. Client characteristics and process issues have been the most frequently researched topic areas, and child-adolescent and adult clients have been participants more often than graduate students. Quantitative designs outnumbered qualitative approaches 2:1 overall, while the number of mixed-methods studies increased considerably. Implications and future directions are provided.